BRAF V600E immunohistochemistry demonstrates that some sessile serrated lesions with adenomatous dysplasia may represent collision lesions. Issue 1 (16th May 2019) - Bettington, Mark; Liu, Cheng; Gill, Anthony; Walker, Neal; Leggett, Barbara; Whitehall, Vicki; Rosty, Christophe
Abstract : Aims: Sessile serrated lesions (SSL) with dysplasia are uncommon polyps with a high risk of rapid malignant transformation. Most of these lesions have a BRAF mutation and 75% show loss of MLH1 expression in their dysplastic component. Different morphological patterns of dysplasia occurring in these polyps have recently been described. We hypothesised that a subset of SSLs with dysplasia mimicking the dysplasia seen in conventional adenoma (adenomatous dysplasia) may represent a collision lesion between an ordinary SSL and a conventional adenoma. Methods and results: We selected 80 SSLs with dysplasia, including 19 with adenomatous dysplasia, 18 with serrated dysplasia and 43 with dysplasia not otherwise specified (NOS). BRAF mutation analysis was performed using molecular testing (allelic discrimination) and the mutation‐specific BRAF‐V600E immunohistochemistry (clone VE1). The overall BRAF‐ V600E mutation rate was 84% in all lesions, 68% in SSLs with adenomatous dysplasia, 89% in SSLs with serrated dysplasia and 88% in SSLs with dysplasia NOS. From the 63 SSLs with dysplasia that were positive for the BRAF‐ V600E mutation, a negative BRAF‐V600E immunostaining was observed in the dysplastic component of 83% of SSLs with adenomatous dysplasia, 0% of SSLs with serrated dysplasia and 3% of SSLs with dysplasia NOS ( P < 0.001). Conclusions: These findings suggest that SSLs with adenomatous dysplasia may not represent advanced SSLs, but instead may be a collision between a non‐dysplastic SSL and a conventional adenoma.